2021
DOI: 10.1002/cam4.3784
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the modified immune prognostic index to prognosticate outcomes in metastatic uveal melanoma patients treated with immune checkpoint inhibitors

Abstract: Background Metastatic uveal melanoma (MUM) is associated with poor survival and inferior response to immune checkpoint inhibitor (ICI) therapy when compared with metastatic cutaneous melanoma. Currently, prognostic biomarkers are lacking to guide treatment decisions. Patients and Methods We conducted a multicenter, retrospective cohort study using a centralized, province‐wide cancer database in Alberta, Canada. We identified 37 patients with histologically confirmed MUM who received at least one dose of single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Our meta-analysis also demonstrated the favorable outcome of disease control rate (DCR) following ICB treatment (Figure S4). Vecchio et al reported immune-related disease control for 36% of patients with metastatic mucosal melanoma, and in most cases, the improved DCR was attributed to SD rather than to a significant reduction in the tumor burden (36). Sander et al (36) showed that beneficial ORR was notable for metastatic UM patients who achieved a PR, and patients having attained either a PR or SD had an improved DCR (36).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our meta-analysis also demonstrated the favorable outcome of disease control rate (DCR) following ICB treatment (Figure S4). Vecchio et al reported immune-related disease control for 36% of patients with metastatic mucosal melanoma, and in most cases, the improved DCR was attributed to SD rather than to a significant reduction in the tumor burden (36). Sander et al (36) showed that beneficial ORR was notable for metastatic UM patients who achieved a PR, and patients having attained either a PR or SD had an improved DCR (36).…”
Section: Discussionmentioning
confidence: 99%
“…Vecchio et al reported immune-related disease control for 36% of patients with metastatic mucosal melanoma, and in most cases, the improved DCR was attributed to SD rather than to a significant reduction in the tumor burden (36). Sander et al (36) showed that beneficial ORR was notable for metastatic UM patients who achieved a PR, and patients having attained either a PR or SD had an improved DCR (36). Moreover, though a modified immune prognostic index (IPI) status might be used to predict a survival benefit from ICB treatment, the IPI score was not found to be associated with ORR and DCR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations